Rawls: Justificação coeretista emergente - Gondim, Elnora; Marra Rodrigues, Osvaldino (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this work show the presence of emerging coherentist justification in the theory of justice as fairness. With this intention, and to facilitate the development of this theme, listed as parameters Rawlsian two notions: (1) the original position and (2) reflective equilibrium.